2022
DOI: 10.1155/2022/8269799
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sleep Intervention Programs during Cardiac Rehabilitation on the Sleep Quality of Heart Patients

Abstract: Background and Objective. Patients with cardiovascular problems experience sleep disorders. Due to the importance of adequate sleep and rest for the growth and repair of damaged cells, it is necessary to use appropriate interventions to improve it. This study determined the effect of sleep intervention programs during cardiac rehabilitation on patients’ sleep quality. Materials and Methods. In this quasi-experimental study with unequal control group design, 35 individuals participated in the cardiac rehabilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It is important to point out that in none of the cited studies were there specific interventions carried out that focused on sleep quality. In a recent study, Ghane et al showed that the addition of a sleep intervention program may lead to clinically significant improvements in sleep quality in CR patients [ 38 ], although further studies are needed to confirm their findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that in none of the cited studies were there specific interventions carried out that focused on sleep quality. In a recent study, Ghane et al showed that the addition of a sleep intervention program may lead to clinically significant improvements in sleep quality in CR patients [ 38 ], although further studies are needed to confirm their findings.…”
Section: Discussionmentioning
confidence: 99%
“…A research study by Ghane et al (2022) investigated the impact of a tailored sleep intervention on the sleep quality and daily functioning of patients with heart failure, demonstrating significant improvements in both sleep quality and ADL performance among those who received the intervention, compared to the control group. 11 These findings underscore the potential benefits of integrating sleep management strategies into the care of heart failure patients. Another study by J Lin et al (2023) explored the associations between demographic factors, sleep quality, and ADL in a cohort of heart failure patients.…”
Section: Introductionmentioning
confidence: 89%